2021
DOI: 10.1590/1807-1929/agriambi.v25n1p23-29
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics of ‘gueroba’ (Syagrus oleracea) fruit pulp

Abstract: The ‘Gueroba’ fruit can be used to produce flours with potential for the development of new products from the ‘Cerrado’ socio-biodiversity. The objective was to estimate the drying kinetics and determine the effective diffusion coefficient and activation energy for the pulp of ‘gueroba’ fruits subjected to different drying temperatures. ‘Gueroba’ fruits were manually pulped, removing the mesocarp with the epicarp, and this material was identified as the pulp. The material was subjected to oven drying at temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…The whole drying process represents a period of decreasing rate. Some previous studies have also found that the drying rate increases with temperature, such as 'gueroba' fruit pulp (Jorge et al, 2021), pear slices (Doymaz & Ismail, 2012), tomato slices (Sadin et al, 2014) and (Cuccurullo et al, 2019).…”
Section: Drying Rate Curvementioning
confidence: 85%
“…The whole drying process represents a period of decreasing rate. Some previous studies have also found that the drying rate increases with temperature, such as 'gueroba' fruit pulp (Jorge et al, 2021), pear slices (Doymaz & Ismail, 2012), tomato slices (Sadin et al, 2014) and (Cuccurullo et al, 2019).…”
Section: Drying Rate Curvementioning
confidence: 85%
“…Considering the Midilli model as the one that best fitted the experimental data, the drying rate constants and the coefficients of the model equation are shown in Table 3. The constant k is related to the effective diffusion and characterizes the implication of the temperatures used on the sample (Jorge et al, 2021). A constant k variation was observed on the drying temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of different plant matrices in the sample probably means that the results of constant k did not have empirical constancy (i.e., a linear reduction of sample moisture with an increase in temperature used in the drying process). Homogeneous samples tend to present continuously increasing k values with an increase in temperature (Jorge et al, 2021; Lima et al, 2021; Tavone et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, la difusividad efectiva en rodajas de calabaza amarga, se estimó en un rango de 8.6293x10-10 y 12.9585x10-10 m 2 s-1 , empleando un secador solar convectivo (Vijayan et al, 2020), mientras que la difusividad efectiva fue de 3.11x10-9 hasta 5.84x10-9 m 2 /s en pulpa de fruto de gueroba con fines de secado y molienda, llevada a cabo a temperaturas entre 40°C y 70°C (Jorge et al, 2021). En otra investigación referente al secado de hojuelas de camotes, la difusividad efectiva hallada por el modelo de difusión de Fick fue entre 2.632x10-9 a 1.596x10-8 m 2 /s (Onwude et al, 2018) y en el pimiento verde la difusividad efectiva fue entre 8.315 x10-8 a 2.363x10-7 m 2 /s en el rango de potencia de microondas investigado (Darvishi et al, 2014), es decir se observa una mayor variación de la difusividad efectiva, lo que concuerda con lo obtenido en el secado de ají jalapeño encurtido, entre 70°C y 10°C.…”
Section: Discussionunclassified